PENINGKATAN KOMPETENSI MAHASISWA TEKNOLOGI MUSIK MELALUI PENERAPAN PEMBELAJARAN SOFTWARE DIGITAL AUDIO WORKSTATION - Andriyanto, R.M Aditya (Universitas Negeri Medan, 2020)
This study aims to determine the process of implementing Digital Audio Workstation learning media software in the Music Technology course in the Study Program of Music Education Music UNJ. In addition, this research is expected to broaden the insight of educators and students (students) about DAW software as a digital literacy of 21st century music education. This research method uses qualitative methods with a participatory action research approach. This study utilizes open interviews to examine and understand the attitudes, views, feelings and behavior of individuals and study groups. Assessing the effectiveness and efficiency of applying DAW software in the production of music. The results showed that music technology courses were arranged to have an important role in integrating technology in education. In addition, the use of technology in learning activities is carried out in an effort to improve the quality of education. Technology is able to provide broad, fast, effective, and efficient access to the dissemination of information to various parts of the world.